The economics of the performing arts before and during the COVID-19 pandemic. Part 1: cost-output-profit analysis on the example of a performance - D. L. Morozova (Вестник университета, 2022)
The article demonstrates the cost-output-profit method possibilities for use by cultural organisations, studies the hypothetical cost recovery possibility from entertainment events, develops practical tools for their financial analytics. Managerial and financial analysis, econometric and graphical construction functions methods have been used. The “proof to the contrary” methods have been applied to investigate the performing arts organisations unprofitability, first substantiated by W. Baumol and W. Bowen. With regard to cultural organisations in the conditions of two-year epidemiological restrictions, a normative threshold occupancy of the hall has been established. Retaining a certain revenue share from ticket sales is not enough to cover current rental costs. In this context, economic performance analytics (operational leverage calculation, break-even analysis) is necessary to analyse the performing arts organisations losses in a pandemic. On the example of the “increased demand” performance, the hypothesis on the existence of a break-even point in which incomes and expenses are balanced has been rejected. The novelty of the study lies in fact that different methods of calculating production costs for theatres have been summarised and a methodology for checking the break-even points existence for organising entertainment events in the long and short term has been presented.